Preparation method of aluminum foil PI composite film with high-density structure and composite film prepared by method

By adopting a multi-layer composite film structure, combining thermoset rigid polyimide composite film, aluminum layer and thermoplastic flexible polyimide adhesive film, the problem of insufficient electromagnetic interference shielding performance in existing polymer-based composite materials is solved, and efficient EMI shielding and good mechanical properties are achieved.

CN119552586APending Publication Date: 2025-03-04NINGBO JINSHAN NEW MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510111888.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing polymer-based composite materials have insufficient performance in electromagnetic interference shielding, and the conductive filler is unevenly dispersed and easy to fall off, which affects the mechanical properties and service life.

Method used

The preparation method of a multi-layer composite film is adopted, including the upper layer of thermoset rigid polyimide composite film, the middle layer of aluminum layer and the lower layer of thermoplastic flexible polyimide adhesive film, the aluminum layer is formed by vacuum sputtering and electroplating, and the EMI shielding and mechanical properties are improved using graphene and silica.

Benefits of technology

It achieves excellent EMI shielding performance, good mechanical properties and high-density structure, effectively preventing oxidation and corrosion of the aluminum layer, and improving the service life of the composite film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum foil PI composite film with a high-density structure and the composite film prepared by the method. The composite film comprises three layers of structures: an upper layer is a thermosetting rigid polyimide composite film, a middle layer is an aluminum layer, and a lower layer is a thermoplastic flexible polyimide adhesive film; the upper layer is prepared from the following raw materials: 4, 4 '-diaminodiphenyl methane (PDA), 3, 3', 4, 4 '-biphenyl tetracarboxylic dianhydride (BPDA), graphene and silicon dioxide; the middle layer is an aluminum layer through vacuum sputtering and electroplating; the lower layer comprises the following raw materials: 3, 3 '-diaminodiphenyl sulfone (3, 3'-DDS), 1, 3-bis (4-aminophenoxy) benzene (1, 3, 4-APB) and 4, 4 '-oxydiphthalic anhydride (ODPA); the cable has the effects that the cable has excellent EMI shielding performance and good mechanical performance; the rigidity and stiffness of the film are effectively improved, the bonding effect is good, and hot-pressing bonding can be directly carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a high-density "sandwich" three-layer aluminum foil PI composite film, wherein the aluminum foil PI composite film is a three-layer structure, wherein the upper layer is a thermosetting polyimide rigid composite film, the middle layer is an aluminum layer, and the lower layer is a thermoplastic polyimide adhesive film. The composite film is resistant to high temperatures, shields electromagnetic interference, has excellent flame retardancy and stability, and can effectively prevent oxidation and corrosion of the aluminum layer in the middle layer. Background Art

[0002] The development of efficient electromagnetic interference (EMI) shielding materials can significantly attenuate electromagnetic waves and effectively protect the normal operation of electronic equipment and human health. Polymer-based composites have been widely used in the field of EMI shielding due to their advantages such as corrosion resistance, low cost and good processing performance. However, most polymer substrates are insulating in nature, which severely limits their application in EMI shielding.

[0003] Currently, researchers can effectively solve the problem of poor EMI shielding performance of polymer-based composites by combining conductive fillers with polymer matrices. However, the problems of uneven dispersion, severe agglomeration, and easy shedding of fillers lead to poor conductivity and magnetic properties of the composite film, which also affects the mechanical properties of the composite film itself, limiting its further development and application in the electronics field. On the other hand, depositing highly conductive metal particles onto the substrate surface through magnetic control, chemical vapor deposition, and core@shell structure technology can also be used to improve the EMI shielding performance of the material, but over time, due to sensitivity to corrosion and mechanical damage, the exposure of the metal functional layer may lead to a decrease in EMI shielding efficiency.

[0004] Among many polymer materials, polyimide (PI) is often used as a matrix for high-performance composites due to its flexibility, good thermal stability and good mechanical properties, and is also considered an excellent candidate substrate for metal particle deposition. Carbon nanotubes, graphene, metal nanowires / particles and MXene are widely used as conductive fillers in polymer-based composites. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a high-density structure aluminum foil PI composite film and a composite film prepared by the method in view of the deficiencies in the prior art.

[0006] In order to achieve the above object, the measures taken by the present invention are: A method for preparing a high-density structural aluminum foil PI composite film. The specific preparation method comprises the following steps: S1. Add N-methylpyrrolidone (NMP) into a reactor. Under nitrogen protection, add 4,4'-diaminodiphenylmethane (PDA) into the reactor. After the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1. Then stir and react at 30℃-40℃ for 2h to obtain a polyamic acid (PAA) resin with a viscosity of 1000-10000cp. S2, dispersing graphene and silicon dioxide in a dispersion respectively, and then mixing them with the resin prepared by the preliminary reaction in step S1, and adjusting the anhydride with dianhydride to obtain a resin, and finally making the molar ratio of dianhydride to diamine 0.95-0.99:1; S3, filtering and vacuum defoaming the resin obtained in step S2, and evenly coating it on a glass plate, heat-treating it at a temperature range of 150-170° C. to obtain a wet film, and then subjecting the wet film to programmed temperature rise to complete imidization to obtain a thermosetting rigid polyimide composite film on the upper layer; S4, by vacuum sputtering and electroplating, a layer of aluminum layer with a thickness of about 10-15 µm is plated on the upper thermosetting rigid polyimide composite film in step S3, that is, a middle aluminum layer is obtained; the vacuum sputtering and electroplating method can not only control the thickness of the aluminum layer, but also make the connection between the aluminum layer and the polyimide film more closely within a certain range, and not easy to fall off; S5. In a non-protonic polar solvent and under nitrogen environment protection, diamine and dianhydride are added to conduct a preliminary reaction, and the molar ratio of dianhydride to diamine is 0.90-0.95:1 to obtain a polyamic acid resin; the resin in step S5 is a thermoplastic resin, and the resin has a good bonding effect and can be directly hot-pressed without additional adhesives. At the same time, its thermal stability is better than that of general adhesives. On the other hand, this layer of thermoplastic polyimide film can also further protect the aluminum layer of the middle layer.

[0007] S6, filtering and vacuum defoaming the resin obtained in step S5, and evenly coating the resin on the middle aluminum layer in step S4 through a coating device to obtain a lower layer of thermoplastic flexible polyimide adhesive film, and finally performing a programmed temperature increase to imidize the resin, and finally obtaining a three-layer high-density aluminum foil PI composite film; Considering universality and operational feasibility, the aprotic polar solvent in steps S1 and S5 is N-methylpyrrolidone (NMP); The diamine in step S1 is 4,4'-diaminodiphenylmethane (PDA), and the dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA); the diamine in step S5 is 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB), the molar ratio of the two diamines is 1:1, and the dianhydride is 4,4'-oxydiphthalic anhydride (ODPA); The graphene in step S2 is added in an amount of 0.3-0.6wt%; the silicon dioxide is used as matte powder, with a particle size of less than 3µm, and is added in an amount of 2wt%; The temperature of the heat treatment during the preparation of the wet film in step S3 is 150-170°C; the program temperature rise in step S3 is specifically: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h; The programmed temperature rise in step S6 is specifically: 70°C-150°C / 1h, 150°C-200°C / 1h, 200°C-220°C / 1h.

[0008] In order to meet the needs of vacuum sputtering, in step S3, the upper thermosetting rigid polyimide composite film uses a rigid monomer to improve the rigidity and stiffness of the film, so that the thickness of the aluminum layer under vacuum sputtering remains consistent. In step S2, before synthesizing the precursor resin, the graphene and silicon dioxide are sheared and dispersed in NMP, and the dispersed powder is ensured to be evenly mixed with the polyimide precursor resin. The added mass percentage of graphene is between 0.3-0.6%, which will help improve the EMI shielding performance of the upper thermosetting rigid polyimide composite film and bring certain thermal conductivity; the added mass percentage of silicon dioxide is 2%, which will help improve the surface roughness of the upper thermosetting rigid polyimide composite film, make the aluminum layer and the polyimide film more closely bonded, and improve the haze of the film, so that the film can play a certain shielding effect. Secondly, a layer of polyimide film on the surface is also beneficial to protect the inner aluminum layer from oxidation, corrosion or shedding.

[0009] The thickness of the upper thermosetting rigid polyimide composite film is 25µm, the thickness of the middle aluminum layer is 10-15µm, and the thickness of the lower thermoplastic flexible polyimide adhesive film is 5µm.

[0010] A composite film, the composite film is made by any of the above methods, The composite film comprises a three-layer structure: an upper layer is a thermosetting rigid polyimide composite film, a middle layer is an aluminum layer, and a lower layer is a thermoplastic flexible polyimide adhesive film; The raw materials of the thermosetting rigid polyimide composite film of the upper layer include 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide; The middle layer is an aluminum layer, which is formed on the surface of the thermosetting rigid polyimide composite film of the upper layer by vacuum sputtering and electroplating, namely, the aluminum layer of the middle layer; The raw materials of the lower thermoplastic flexible polyimide adhesive film include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA).

[0011] The beneficial effects of the present invention are as follows: (1) The present invention combines the advantages of blending and metal surface deposition through a multi-layer composite method, so that the composite film has excellent EMI shielding performance and good mechanical properties, and at the same time, it also has certain operability in production.

[0012] (2) The upper layer of the thermosetting rigid polyimide composite film of the present invention uses a rigid monomer, which effectively improves the rigidity and stiffness of the film, so that the thickness of the aluminum layer under vacuum sputtering can be kept as consistent as possible; and the addition of a small amount of graphene can make the upper polyimide film have a certain EMI shielding performance, while bringing a certain thermal conductivity, and will not affect the mechanical and electrical properties of the film; the addition of silicon dioxide is beneficial to improving the surface energy of the upper polyimide film, making the aluminum layer and the polyimide film more tightly bonded, and increasing the haze of the film, so that the film can have a certain shielding effect.

[0013] (3) The thermoplastic flexible polyimide adhesive film of the middle and lower layers of the present invention is prepared by thermoplastic resin. The film has a good bonding effect and can be directly hot-pressed without the need for additional adhesives. At the same time, its thermal stability is better than that of general adhesives, which is more beneficial for protecting the aluminum layer of the middle layer.

[0014] (4) By designing this "sandwich" three-layer structure, the two layers of polyimide film can not only play their respective advantages, but also effectively protect the middle aluminum layer, thereby improving the service life of the composite film. DETAILED DESCRIPTION

[0015] A method for preparing a high-density structure aluminum foil PI composite film, the composite film comprises a three-layer structure: an upper layer is a thermosetting rigid polyimide composite film, a middle layer is an aluminum layer, and a lower layer is a thermoplastic flexible polyimide adhesive film; The raw materials of the upper thermosetting rigid polyimide composite film include 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide. First, PDA and BPDA are used to synthesize a polyamic acid precursor in N-methylpyrrolidone (NMP), and graphene and silicon dioxide are added in the middle step. Finally, a two-step thermal imidization method is used to obtain the upper thermosetting rigid polyimide composite film. The middle layer is an aluminum layer, which is formed by vacuum sputtering and electroplating on the surface of the thermosetting rigid polyimide composite film of the upper layer with a thickness of 10-15µm, i.e., the aluminum layer of the middle layer; The raw materials of the thermoplastic flexible polyimide adhesive film of the lower layer include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA). First, 3,3'-DDS, 1,3,4-APB and ODPA are used to synthesize a polyamic acid precursor resin in N-methylpyrrolidone (NMP). The resin is coated on the surface of the aluminum layer of the middle layer by coating, so that it is thermally imidized and cured to form the thermoplastic flexible polyimide adhesive film of the lower layer. The specific preparation method comprises the following steps: S1. Add N-methylpyrrolidone (NMP) into a reactor. Under nitrogen protection, add 4,4'-diaminodiphenylmethane (PDA) into the reactor. After the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1. Then stir and react at 30℃-40℃ for 2h to obtain a polyamic acid (PAA) resin with a viscosity of 1000-10000cp. S2, dispersing graphene and silicon dioxide in a dispersion respectively, and then mixing them with the resin prepared by the preliminary reaction in step S1, and adjusting the anhydride with dianhydride to obtain a resin, and finally making the molar ratio of dianhydride to diamine 0.95-0.99:1; S3, filtering and vacuum defoaming the resin obtained in step S2, and evenly coating it on a glass plate, heat-treating it at a temperature range of 150-170° C. to obtain a wet film, and then subjecting the wet film to programmed temperature rise to complete imidization to obtain a thermosetting rigid polyimide composite film on the upper layer; S4, by vacuum sputtering and electroplating, a layer of aluminum layer with a thickness of about 10-15 μm is plated on the upper thermosetting rigid polyimide composite film in step S3, so as to obtain a middle aluminum layer; S5, adding diamine and dianhydride in a non-protonic polar solvent and under nitrogen environment protection, and conducting a preliminary reaction, wherein the molar ratio of dianhydride to diamine is 0.90-0.95:1, to obtain a polyamic acid resin; S6. Filter and vacuum defoam the resin obtained in step S5, and evenly apply the resin to the middle aluminum layer in step S4 through a coating device to obtain a lower layer of thermoplastic flexible polyimide adhesive film. Finally, program the temperature to imide the resin, and finally obtain a three-layer high-density structural aluminum foil PI composite film.

[0016] The aprotic polar solvent in steps S1 and S5 is N-methylpyrrolidone (NMP).

[0017] The diamine in step S1 is 4,4'-diaminodiphenylmethane (PDA), and the dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA); the diamine in step S5 is 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB), the molar ratio of the two diamines is 1:1, and the dianhydride is 4,4'-oxydiphthalic anhydride (ODPA).

[0018] The graphene in step S2 is added in an amount of 0.3-0.6wt%; the silicon dioxide is used as a matte powder with a particle size less than 3µm and is added in an amount of 2wt%.

[0019] The heat treatment temperature when preparing the wet film in step S3 is 150-170°C; the programmed temperature rise in step S3 is specifically: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h.

[0020] The programmed temperature rise in step S6 is specifically: 70°C-150°C / 1h, 150°C-200°C / 1h, 200°C-220°C / 1h.

[0021] The thickness of the upper thermosetting rigid polyimide composite film is 25µm, the thickness of the middle aluminum layer is 10-15µm, and the thickness of the lower thermoplastic flexible polyimide adhesive film is 5µm.

[0022] The high-density structured aluminum foil PI composite film prepared by the method of the present invention has an EMI shielding performance of 45-58 dB, and a film elongation at break greater than 30%. In addition, the composite film has an excellent flame retardant effect and excellent high temperature resistance. The upper thermosetting rigid polyimide composite film not only plays an insulating and heat-resistant role, but also has a certain EMI shielding effect and thermal conductivity, and the lower thermoplastic flexible polyimide adhesive film can play a bonding role. At the same time, the structure of the upper and lower polyimide films also effectively protects the aluminum layer of the middle layer, improving its anti-oxidation and corrosion resistance.

[0023] According to the above steps, the preferred embodiments of the present invention are further described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] In order to fully illustrate the purpose of the present invention, the present invention is further described in detail through specific implementation cases, but this specific embodiment is only used as an explanation of the present invention and does not limit the scope of protection involved in the present invention. Those skilled in the art should not violate the spirit of the present invention on the basis of understanding the technical solution of the present invention, and modifications or replacements based on a certain scope should all be covered within the scope of protection of the present invention. Embodiment 1:

[0025] The present embodiment provides a method for preparing a high-density structure aluminum foil PI composite film. Since it has a three-layer structure similar to a sandwich structure, it is also called a method for preparing a high-density "sandwich" structure aluminum foil PI composite film. The upper layer is a thermosetting rigid polyimide composite film, including raw materials such as 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide. First, PDA and BPDA are used to synthesize a polyamic acid precursor in N-methylpyrrolidone (NMP), and graphene and silicon dioxide are added in the middle step. Finally, a two-step thermal imidization method is used to obtain a thermosetting rigid polyimide film, which is the thermosetting rigid polyimide film of the upper layer. Polyimide composite film; the middle layer is an aluminum layer, and a layer of aluminum layer of about 10-15µm is formed on the surface of the upper layer by vacuum sputtering and electroplating; the lower layer is a thermoplastic flexible polyimide adhesive film, including raw materials such as 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA). First, 3,3'-DDS, 1,3,4-APB and ODPA are used to synthesize a polyamic acid precursor resin in N-methylpyrrolidone (NMP), and the resin is coated on the surface of the aluminum layer by coating, so that it is thermally imidized and cured to form a thermoplastic flexible polyimide adhesive film of the lower layer. The specific preparation method includes the following steps: S1: Add 500 mL of N-methylpyrrolidone (NMP) into a reactor, add 4,4'-diaminodiphenylmethane (PDA) into the reactor under nitrogen protection, and after the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1; then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp; S2: adding graphene dispersion and silica dispersion to the PAA solution prepared in step S1, wherein the mass proportion of graphene in the film is 0.3%, and the mass proportion of silica in the film is 2%, and after stirring evenly, BPDA is used to adjust the anhydride so that the final molar ratio of dianhydride to diamine is 0.95-0.99:1, and the reaction is stirred at 40°C for 4h to obtain a uniform precursor resin; S3: After filtering, remove the larger particle impurities, and then vacuum defoam, the precursor resin is scraped onto a clean glass plate, and a wet film is prepared at 150-170°C. After obtaining the wet film, the wet film is fixed on a nail plate for imidization. The specific imidization heating program is: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h, and finally the upper layer of thermosetting rigid polyimide composite film is obtained, and its thickness is 25µm; S4: by vacuum sputtering and electroplating, a 10µm aluminum layer, i.e., a middle aluminum layer, is plated on the upper thermosetting rigid polyimide composite film in step S3; S5. Add 500 mL of N-methylpyrrolidone (NMP) into the reactor. Under nitrogen protection, add 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) into the reactor. The molar ratio of the two diamines is 1:1. After the diamines are completely dissolved, add 4,4'-oxydiphthalic anhydride (ODPA) into the reactor to make the molar ratio of dianhydride to diamine 0.90-0.95:1. Then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp. S6. Filter and vacuum defoam the resin obtained in step S5, and evenly apply the resin to the aluminum layer of the sample obtained in step S4 through a coating device. Finally, perform a temperature program to imidize the resin to obtain the final "sandwich" structure aluminum foil PI composite film. The specific temperature program is: 70℃-150℃ / 1h, 150℃-200℃ / 1h, 200℃-220℃ / 1h. The thickness of the coated polyimide layer (C layer) is 5µm.

[0026] The thickness of the aluminum foil PI composite polyimide film prepared above is about 40 μm. After testing, the EMI shielding performance of the composite polyimide film obtained is 45 dB, the elongation at break is 47%, and the tensile strength reaches 150 MPa. Embodiment 2:

[0027] The present embodiment provides a method for preparing a high-density structure aluminum foil PI composite film. Since it has a three-layer structure similar to a sandwich structure, it is also called a method for preparing a high-density "sandwich" structure aluminum foil PI composite film. The upper layer is a thermosetting rigid polyimide composite film, including raw materials such as 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide. It is characterized in that PDA and BPDA are first used to synthesize a polyamic acid precursor in N-methylpyrrolidone (NMP), graphene and silicon dioxide are added in the middle step, and finally a two-step thermal imidization method is used to obtain a thermosetting rigid polyimide film, that is, the upper layer is thermally bonded to the film. The invention discloses a thermoplastic rigid polyimide composite film; the middle layer is an aluminum layer, and a 10-15µm aluminum layer is formed on the upper surface by vacuum sputtering and electroplating, namely, the middle aluminum layer; the lower layer is a thermoplastic flexible polyimide adhesive film, including raw materials such as 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA), characterized in that 3,3'-DDS, 1,3,4-APB and ODPA are first used to synthesize a polyamic acid precursor resin in N-methylpyrrolidone (NMP), and the resin is coated on the surface of the aluminum layer by coating, so that it is thermally imidized and cured (C layer). The specific preparation method includes the following steps: S1: Add 500 mL of N-methylpyrrolidone (NMP) into a reactor, add 4,4'-diaminodiphenylmethane (PDA) into the reactor under nitrogen protection, and after the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1; then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp; S2: adding graphene dispersion and silica dispersion to the PAA solution prepared in step S1, wherein the mass proportion of graphene in the film is 0.6%, and the mass proportion of silica in the film is 2%, and after stirring evenly, BPDA is used to adjust the anhydride so that the final molar ratio of dianhydride to diamine is 0.95-0.99:1, and the reaction is stirred at 40°C for 4h to obtain a uniform precursor resin; S3: After filtering, remove the larger particle impurities, and then vacuum defoam, the precursor resin is scraped onto a clean glass plate, and a wet film is prepared at 150-170°C. After obtaining the wet film, the wet film is fixed on a nail plate for imidization. The specific imidization heating program is: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h, and finally the upper layer of thermosetting rigid polyimide composite film is obtained, and its thickness is 25µm; S4: by vacuum sputtering and electroplating, a 10µm aluminum layer is plated on the upper thermosetting rigid polyimide composite film in step S3, i.e., the middle aluminum layer; S5. Add 500 mL of N-methylpyrrolidone (NMP) into the reactor. Under nitrogen protection, add 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) into the reactor. The molar ratio of the two diamines is 1:1. After the diamines are completely dissolved, add 4,4'-oxydiphthalic anhydride (ODPA) into the reactor to make the molar ratio of dianhydride to diamine 0.90-0.95:1. Then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp. S6. Filter and vacuum defoam the resin obtained in step S5, and evenly apply the resin to the aluminum layer of the sample obtained in step S4 through a coating device. Finally, program the temperature to imide the resin to obtain the final "sandwich" structure aluminum foil PI composite film. The specific program temperature is: 70℃-150℃ / 1h, 150℃-200℃ / 1h, 200℃-220℃ / 1h. The thickness of the coated polyimide layer (lower layer) is 5µm.

[0028] The thickness of the aluminum foil PI composite polyimide film prepared above is about 40 μm. After testing, the EMI shielding performance of the composite polyimide film obtained is 49 dB, the elongation at break is 45%, and the tensile strength reaches 143 MPa. Embodiment 3:

[0029] The present embodiment provides a method for preparing a high-density structure aluminum foil PI composite film. Since it has a three-layer structure similar to a sandwich structure, it is also called a method for preparing a high-density "sandwich" structure aluminum foil PI composite film. The upper layer is a thermosetting rigid polyimide composite film, including raw materials such as 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide. It is characterized in that a polyamic acid precursor is first synthesized using PDA and BPDA in N-methylpyrrolidone (NMP), graphene and silicon dioxide are added in the middle step, and finally a two-step thermal imidization method is used to obtain the upper layer of the thermosetting rigid polyimide composite film; The upper layer is an aluminum layer, and a layer of aluminum layer of about 10-15µm is formed on the upper surface by vacuum sputtering and electroplating, that is, the middle aluminum layer; the lower layer is a thermoplastic flexible polyimide adhesive film, including raw materials such as 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA), characterized in that 3,3'-DDS, 1,3,4-APB and ODPA are first used to synthesize a polyamic acid precursor resin in N-methylpyrrolidone (NMP), and the resin is coated on the surface of the aluminum layer by coating, so that it is thermally imidized and cured to form a lower thermoplastic flexible polyimide adhesive film. The specific preparation method includes the following steps: S1: Add 500 mL of N-methylpyrrolidone (NMP) into a reactor, add 4,4'-diaminodiphenylmethane (PDA) into the reactor under nitrogen protection, and after the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1; then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp; S2: adding graphene dispersion and silica dispersion to the PAA solution prepared in step S1, wherein the mass proportion of graphene in the film is 0.6%, and the mass proportion of silica in the film is 2%, and after stirring evenly, BPDA is used to adjust the anhydride so that the final molar ratio of dianhydride to diamine is 0.95-0.99:1, and the reaction is stirred at 40°C for 4h to obtain a uniform precursor resin; S3: After filtering, remove the larger particle impurities, and then vacuum defoam, the precursor resin is scraped onto a clean glass plate, and a wet film is prepared at 150-170°C. After the wet film is obtained, the wet film is fixed on a nail plate for imidization. The specific imidization heating program is: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h, and finally the upper layer is a thermosetting rigid polyimide composite film with a thickness of 25µm; S4: by vacuum sputtering and electroplating, a 15µm aluminum layer, i.e., a middle aluminum layer, is plated on the upper thermosetting rigid polyimide composite film in step S3; S5. Add 500 mL of N-methylpyrrolidone (NMP) into the reactor. Under nitrogen protection, add 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) into the reactor. The molar ratio of the two diamines is 1:1. After the diamines are completely dissolved, add 4,4'-oxydiphthalic anhydride (ODPA) into the reactor to make the molar ratio of dianhydride to diamine 0.90-0.95:1. Then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp. S6. Filter and vacuum defoam the resin obtained in step S5, and evenly apply the resin to the aluminum layer of the sample obtained in step S4 through a coating device. Finally, program the temperature to imide the resin to obtain the final "sandwich" structure aluminum foil PI composite film. The specific program temperature is: 70℃-150℃ / 1h, 150℃-200℃ / 1h, 200℃-220℃ / 1h. The thickness of the coated polyimide layer (lower layer) is 5µm.

[0030] The thickness of the aluminum foil PI composite polyimide film prepared above is about 45 μm. After testing, the EMI shielding performance of the composite polyimide film obtained is 58 dB, the elongation at break is 55%, and the tensile strength reaches 152 MPa.

[0031] Comparison case: This embodiment provides a conventional method for preparing a graphene-doped polyimide film, characterized in that PDA and BPDA are used to synthesize a polyamic acid precursor in N-methylpyrrolidone (NMP), graphene is added in an intermediate step, and finally a two-step thermal imidization method is used to obtain a thermosetting shielding polyimide film. The specific preparation method includes the following steps: S1: Add 500 mL of N-methylpyrrolidone (NMP) into a reactor, add 4,4'-diaminodiphenylmethane (PDA) into the reactor under nitrogen protection, and after the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:1; then stir and react at 30℃-40℃ for 2 h to obtain a polyamic acid (PAA) homogeneous solution with a viscosity of 1000-10000cp; S2: adding graphene dispersion to the PAA solution prepared in step S1, wherein the mass proportion of graphene in the film is 2%, stirring evenly, adjusting anhydride with BPDA, so that the final molar ratio of dianhydride to diamine is 0.95-0.99:1, stirring and reacting at 40°C for 4h, to obtain a uniform precursor resin; S3: After filtering, remove larger particle impurities, and then vacuum defoam, the precursor resin is scraped onto a clean glass plate, and wet film is prepared at 150-170°C. After obtaining the wet film, the wet film is fixed on a nail plate for imidization. The specific imidization heating program is: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h; The thickness of the polyimide film for shielding prepared above is about 40 μm. After testing, the EMI shielding performance of the obtained polyimide film is 16 dB, the elongation at break is 31%, and the tensile strength reaches 122 MPa.

[0032] A composite membrane, the composite membrane is prepared by any of the above methods, The composite film comprises a three-layer structure: an upper layer is a thermosetting rigid polyimide composite film, a middle layer is an aluminum layer, and a lower layer is a thermoplastic flexible polyimide adhesive film; The raw materials of the thermosetting rigid polyimide composite film of the upper layer include 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide; The middle layer is an aluminum layer, which is formed on the surface of the thermosetting rigid polyimide composite film of the upper layer by vacuum sputtering and electroplating, namely, the aluminum layer of the middle layer; The raw materials of the lower thermoplastic flexible polyimide adhesive film include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA).

[0033] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any equivalent modifications and substitutions made by any technician familiar with the technical field within the technical scope disclosed by the present invention and based on the technical solution and inventive concept of the present invention are all covered by the protection scope and disclosure scope defined by the claims of the present invention.

Claims

1. A method for preparing a high-density structured aluminum foil PI composite film, characterized in that: The steps include: S1. Add N-methylpyrrolidone (NMP) into a reactor. Under nitrogen protection, add 4,4'-diaminodiphenylmethane (PDA) into the reactor. After the diamine is completely dissolved, add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) into the reactor to make the molar ratio of dianhydride to diamine be 0.90-0.95:

1. Then stir and react at 30℃-40℃ for 2h to obtain a polyamic acid (PAA) resin with a viscosity of 1000-10000cp. S2, dispersing graphene and silicon dioxide in a dispersion respectively, and then mixing them with the resin prepared by the preliminary reaction in step S1, and adjusting the anhydride with dianhydride to obtain a resin; S3, filtering and vacuum defoaming the resin obtained in step S2, and evenly coating it on a glass plate, heat-treating it at a temperature range of 150-170° C. to obtain a wet film, and then subjecting the wet film to programmed temperature rise to complete imidization to obtain a thermosetting rigid polyimide composite film on the upper layer; S4, plating an aluminum layer on the upper thermosetting rigid polyimide composite film in step S3 by vacuum sputtering and electroplating, so as to obtain a middle aluminum layer; S5, adding diamine and dianhydride in a non-protonic polar solvent and under nitrogen environment protection, and conducting a preliminary reaction to obtain a polyamic acid resin; S6. Filter and vacuum defoam the resin obtained in step S5, and evenly apply the resin to the middle aluminum layer in step S4 through a coating device to obtain a lower layer of thermoplastic flexible polyimide adhesive film. Finally, program the temperature to imide the resin, and finally obtain a three-layer high-density structural aluminum foil PI composite film.

2. The method for preparing a high-density structured aluminum foil PI composite film according to claim 1, characterized in that: The aprotic polar solvent in steps S1 and S5 is N-methylpyrrolidone (NMP).

3. The method for preparing a high-density structure aluminum foil PI composite film according to claim 2, characterized in that: The diamine in step S1 is 4,4'-diaminodiphenylmethane (PDA), and the dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA); the diamine in step S5 is 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB), the molar ratio of the two diamines is 1:1, and the dianhydride is 4,4'-oxydiphthalic anhydride (ODPA).

4. The method for preparing a high-density structured aluminum foil PI composite film according to claim 3, characterized in that: The graphene in step S2 is added in an amount of 0.3-0.6wt%; the silicon dioxide is used as a matte powder with a particle size less than 3µm and is added in an amount of 2wt%.

5. The method for preparing a high-density structure aluminum foil PI composite film according to claim 4, characterized in that: The heat treatment temperature when preparing the wet film in step S3 is 150-170°C; the programmed temperature rise in step S3 is specifically: 70°C-160°C / 1h, 160°C-300°C / 1h, 300°C-370°C / 1h.

6. The method for preparing a high-density structured aluminum foil PI composite film according to claim 5, characterized in that: The programmed temperature rise in step S6 is specifically: 70°C-150°C / 1h, 150°C-200°C / 1h, 200°C-220°C / 1h.

7. The method for preparing a high-density structured aluminum foil PI composite film according to claim 6, characterized in that: The thickness of the upper thermosetting rigid polyimide composite film is 25µm, the thickness of the middle aluminum layer is 10-15µm, and the thickness of the lower thermoplastic flexible polyimide adhesive film is 5µm.

8. The method for preparing a high-density structure aluminum foil PI composite film according to claim 1, characterized in that: In the upper layer of thermosetting rigid polyimide composite film, PDA and BPDA are first used to synthesize a polyamic acid precursor in N-methylpyrrolidone (NMP), graphene and silicon dioxide are added in the middle step, and finally a two-step thermal imidization method is used to obtain the upper layer of thermosetting rigid polyimide composite film; the thickness of the aluminum layer is 10-15µm; in the lower layer of thermoplastic flexible polyimide adhesive film, 3,3'-DDS, 1,3,4-APB and ODPA are first used to synthesize a polyamic acid precursor resin in N-methylpyrrolidone (NMP), and the resin is coated on the surface of the aluminum layer in the middle layer by coating, so that it is thermally imidized and cured to form the thermoplastic flexible polyimide adhesive film in the lower layer.

9. The method for preparing a high-density structured aluminum foil PI composite film according to claim 8, characterized in that: In the S1, the molar ratio of dianhydride to diamine is 0.90-0.95:1; in the S2, the final molar ratio of dianhydride to diamine is 0.95-0.99:1; in the S4, the thickness of the aluminum layer is 10-15µm; in the S5, the molar ratio of dianhydride to diamine is 0.90-0.95:

1.

10. A composite film, characterized in that: The composite film is prepared by the preparation method described in any one of claims 1 to 9 above. The composite film comprises a three-layer structure: an upper layer is a thermosetting rigid polyimide composite film, a middle layer is an aluminum layer, and a lower layer is a thermoplastic flexible polyimide adhesive film; The raw materials of the thermosetting rigid polyimide composite film of the upper layer include 4,4'-diaminodiphenylmethane (PDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), graphene and silicon dioxide; The middle aluminum layer is formed on the surface of the upper thermosetting rigid polyimide composite film by vacuum sputtering and electroplating, i.e., the middle aluminum layer; The raw materials of the lower thermoplastic flexible polyimide adhesive film include 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 1,3-bis(4-aminophenoxy)benzene (1,3,4-APB) and 4,4'-oxydiphthalic anhydride (ODPA).

Citation Information

Patent Citations

  • High-hardness polyimide film capable of being thermally pressed and preparation method thereof

    CN112646222A

  • Method for manufacturing shielding material

    CN112689454A

  • Polyimide composite film having excellent electromagnetic wave shielding performance, and manufacturing method therefor

    CN112969587A

  • High-thermal-conductivity electromagnetic shielding polyimide-based co-carbonized carbon fiber composite material and preparation method thereof

    CN115286823A

  • Polyimide aluminum foil composite film as well as preparation method and application thereof

    CN117584576A